KEBIJAKAN PEMERINTAH KOTA SURABAYA DALAM PENUMBUHAN BUDAYA BACA DI KALANGAN PELAJAR - Herman Hendrik; Lukman Solihin; Noviyanti Noviyanti; Indah Pratiwi; Kaisar Julizar (Jurnal Ilmiah Mimbar Demokrasi, 2017)
This article is aimed at describing the role of Surabaya City Administration in nurturing the culture of reading. Presevious studies show that literacy level in Indonesia is relatively low. Inspite of its achievement in eradicating illiteracy, Indonesia has not managed nurturing the culture of reading. In decentralization era, local governments (provincial and regency/city) have vital roles in policy making. They have wider spaces for innovations and creativities in developing their societies and regions, based on the authorities that the central government transferred to them. This context made it possible for the Surabaya City Administration to make policies supporting the nurturing of the culture of reading. This article is based on a field research using qualitative method conducted in Surabaya City. The data of the research resulted from interviews with relevant parties, they are personnel of the Office of Educational Affairs of Surabaya City and the Board of Archive and Library of Surabaya City, and also desk studies. The findings of the research show that in the middle of limited policy instruments available for nurturing literacy, especially nurturing the culture of reading, Surabaya City Administration declared itself as a â€œcity of literacyâ€, followed by many policies supporting the development of literacy. Those policies are the issuance of literacy-supporting regulations, synergy among related government agencies, human resources development, implementation of literacy events, and education ecosystem envionment. The result of the policies is the increase in the reading interest of the people supported by sustainable literacy programs.